UPLC-QTOF-MS/MS analysis and antibacterial activity of the Manilkara zapota (L.) P. Royen against Escherichia coli and other MDR bacteria - Freitas, Thiago S.; Campina, Fábia F.; Costa, Maria S.; Rocha, Janaína E.; Cruz, Rafael P.; Pinheiro, Jacqueline C. A.; Pereira-Júnior, Francisco N.; Lima, Micheline A.; Pires de Sá, Maísa Freire Cartaxo; Teixeira, Alexandre M.R.; Coutinho, Henrique D.M. (Cellular and Molecular Biology, 2021)
With the spread of bacterial resistance against clinically used antibiotics, natural plant-derived products are being studied as new sources of antibacterial molecules. Manilkara zapota is a common plant species in the American continent that is used as a food source. Studies show the M. zapota extract is rich in phenolic substances that can serve as basic molecules for the pharmaceutical industry. An extract from fresh M. zapota leaves was produced and tested to identify the compounds present, as well as its direct antibacterial and clinical antibiotic modulatory activities. To analyze the results, a new statistical methodology based on the Shannon-Wiener index was tested, capable of correcting distortions in heterogeneous environments. The Hydroethanolic Extract of Manilkara zapota leaves (HEMzL) presented a wide variety of phenolic products, as well as tannins, in the UPLC analysis. The extract showed direct antibacterial activity against the standard Staphylococcus aureus strain, however, it either acted antagonistically when associated with the tested antibiotics, or it did not present statistical significance when compared to the control. This demonstrates a need to be cautious when associating natural products with antibiotics for clinical use, as a hindrance to infectious treatments may occur. As for the statistical analysis mechanism tested, this proved to be effective, reducing false negatives at low antibiotic concentrations and false positives at high concentrations in the microdilution plate.